Urban Design Governance Soft powers and the European experience - Carmona, Matthew (UCL Press, 2023)
Urban Design Governance takes a deep dive into the governance of urban design around Europe. It examines interventions in the means and processes of designing the built environment as devised by public authorities and other stakeholders across the continent. In particular, the focus is on the use of soft powers and allied financial mechanisms to influence design quality in the public interest. In doing so, the book traces the scope, use and effectiveness of the range of informal (non-regulatory) urban design governance tools that governments, municipalities and others have at their disposal. Developed from the Urban Maestro project, a joint initiative of the United Nations Human Settlement programme (UN-Habitat), UCL and the Brussels Bouwmeester Maître Architecte (BMA), Urban Design Governance offers the first panorama of informal urban design governance tools from across Europe, and places the tools within a theoretical and analytical framework with the potential to be applied locally and internationally. Last, the book discusses and reveals the essential pre-requisites for the effective governance of urban design. Governments everywhere are increasingly seeing these sorts of tools as part of a necessary investment in delivering the high-quality built environments that their residents, businesses and investors demand. This book shows how.